Hero-Somnambulist in V. V. Nabokov’s Novel “Transparent Things” - E. G. Nikolayeva (Научный диалог, 2019)
The article is devoted to the study of the features of the hero-somnambulist in V. V. Nabokov’s novel “Transparent Things” and the specifics of the writer’s appeal to the theme of magnetism and somnambulism in his works. The study briefly examines the history of the formation of sustainable interest in this topic in Europe, the United States and Russia in the 18th-20th centuries. The review of literary works concerning the theme of sleepwalking in Nabokov’s works and the reasons for the writer’s appeal to it is carried out. The paper shows the connection between somnambulism and ‘automatism,” “mechanicalness,” which Nabokov often refers to romantic tradition and German cinema. The article describes the ways of introducing the “magic” and its functions into the novel. In particular, special attention is paid to the intertextual potential of the fragments associated with magnetism, levitation, sleepwalking, etc. Reminiscences of the works by M. Yu. Lermontov, F. M. Dostoevsky, L. N. Tolstoy, F. Sologub are described. The emphasis is on the metaliterature comprehension of a number of fragments related to the motives of sleep and death. The specificity of the implementation in the novel of paradigm of sleep - death - flight - creativity and opposition gravity ( earth’s gravity ) - lightness ( flight ) is revealed.